Nerve ultrasound in amyotrophic lateral sclerosis: systematic review and meta-analysis - Abdelnaby, Ramy; Shabib, Ahmed Samy; El Din Moawad, Mostafa Hossam; Salem, Talal; Wagih Youssef Awad, Merna; Awad, Peter Dawoud; Maallem, Imene; Atwan, Hany; Rabie, Salma Adel; Mohamed, Khaled Ashraf; Abdelmageed, Hossam; Karkour, Ali M; et al. (Neurological research and practice, 2024)
BACKGROUND/ AIM: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease affecting upper and lower motor neurons, causing progressive atrophy of muscles, hypertonia, and paralysis. This study aimed to evaluate the current evidence and effectiveness of ultrasound in investigating nerve cross-sectional area (CSA) of peripheral nerves, vagus and cervical roots in those with ALS compared with healthy controls and to pool the CSA measurements. METHODS: A systematic search was conducted on Cochrane, Clarivate Web of Science, PubMed, Scopus, and Embase for the mesh terms nerve, ultrasonography, and amyotrophic lateral sclerosis. A quality assessment was performed using the New-Ottawa scale. In addition, a double-arm meta-analysis using Review Manager 5 software version 5.4 was performed. RESULTS: From the seventeen studies included in this review, the overall mean difference showed that individuals with ALS had a significantly smaller CSA in comparison to healthy controls for median, ulnar, C6 root, and phrenic nerves. However, no significant difference in the CSA was found in radial, vagal, sural, and tibial nerves. DISCUSSION: This study confirmed results of some of the included studies regards the anatomic sites, where nerve atrophy in ALS could be detected to potentially support the diagnosis of ALS. However, we recommend further large, prospective studies to assess the diagnostic value of these anatomical sites for the diagnosis of ALS. CONCLUSIONS: Our findings confirmed specific anatomic sites to differentiate ALS patients from healthy controls through ultrasound. However, these findings cannot be used to confirm the ALS diagnosis, but rather assist in differentiating it from other diagnoses. TRIAL REGISTRATION: Retrospectively registered on July 30th 2024 in PROSPERO (PROSPERO (york.ac.uk)) with ID574702.